Impact of Drilling Speed and Osteotomy Technique (Primary Bone Healing) on Dental Implant Preparation: An In Vitro Study Using Polyurethane Foam - Luca Comuzzi; Margherita Tumedei; Tea Romasco; Alessandro Cipollina; Giulia Marchioli; Adriano Piattelli; Natalia Di Pietro (Osteology, 2025)
Background/Objectives: The achievement of primary stability in low-density bone represents a critical endpoint in clinical practice. The aim of the present investigation was to evaluate the effectiveness of different drilling osteotomy techniques on polyurethane bone substitutes in vitro. Methods: A total of 320 osteotomies have been conducted on 10 pound per cubic feet (PCF) and 20PCF, respectively, with and without cortical layer. The simultaneous and progressive drilling protocol has been conducted at two different rotational speeds considering two different implant profiles (TAC conical vs. NT cylindrical implants). The study variables were insertion torque, removal torque, and resonance frequency analysis (RFA). Results: A significantly higher insertion torque, removal torque, and resonance frequency analysis RFA was detected at low speed with simultaneous drilling protocol (RPM) (p < 0.05). A TAC implant produced an increased implant stability compared to NT implants in all conditions tested (p < 0.05). Conclusions: The conical TAC implant showed higher implant stability in low-density polyurethane, and it is strongly recommended in critical bone quality. Simultaneous drilling osteotomy at low speed could further improve torquing positioning and significantly achieve primary stability in this condition.